Cadeias de suprimentos de produtos de luxo: proposta de estruturação da literatura e avaliação do valor do lead time - Brandão, Maicom Sergio (2019)
The present study aims to value lead time in a luxury product supply chain. Lead time could be seen as an important element in a responsive supply chain strategy while responsiveness is the ability of reacting to unexpected changes in demand in order to reduce stock-outs, obsolescence and promotions in the most efficient way. Thus, first of all, we searched for empirical and theoretical evidences that responsiveness is an important strategy to supply chain management applied to luxury products. In theoretical domains, we conducted a systematic literature review that revealed that responsiveness is an important strategy to meet the critical success factors of luxury industry and affects supply chain configurations, in special, actors, group of products, location and outsourcing level. In empirical side, we conducted an action-research that showed that lead time is an important variable when demand uncertainty is high and it is related to operational costs as inventory, transportation and lost sales. To value lead time, we expanded the original model created by Blackburn (2012) in which the central element is the MVT, i.e. the marginal value of time that represents the variation in inventory costs per unit when occurs a variation in lead time. We added elements of supply chain management applied to luxury products in the original model and applied it in a real case. The results showed that MVT is high to luxury products comparing to functional ones. Finally, MVT can be used as a tool to help in decision-making process in themes of supply chain management such as manufacturing/vendor/distribution location or logistical choices.